The extent of compliance and application of safety and security standards in scientific laboratories – Case study of Ramla Secondary School, Palestine - - Eltarshawi, Etemad Abdulaziz; Azzam, Esraa Mosbah (Journal of Risk and Crisis Management, 2021)
The study aimed to identify safety and security standards within the school laboratory and to reveal the extent of the knowledge of teachers and science supervisors about the health and safety systems applied within the laboratory, and the researchers followed the descriptive analysis methodology using the personal interview tool and the number of study sample individuals 7 employees in Ramla High School from science teachers and supervisors The laboratory technician, and the study reached a set of results, the most important of which are the identification of safety and security standards within the school laboratory, revealing the extent of the knowledge of teachers and supervisors of science about health and safety systems applied within the laboratory, signs and clear signs are available for hazardous and chemical materials, quantities are not used when conducting scientific experiments There is no special clothing for protection. Among the most important recommendations: The safety and security procedures must be followed. The initial follow-up by the Ministry of Education is necessary. Safety signs and signals must be available from hazardous materials.